Anestésicos locales en cirugía podológica - Trepal, Michael J.; Jules, Kevin T. (Revista Internacional de Ciencias Podológicas, 2007)
The authors present a review of the clinical handling of the use of local anesthetics in podiatry, as well as the pharmacology, the factors that determine the clinical action of the anesthetics, the toxicity to the anesthesia, allergy, its prevention and treatment, as well as the techniques of anesthesia infiltration.